Configuring a supply network in the presence of volume discounts - Ma, Liping; Zhang, Guoqing (Journal of manufacturing systems, 2008)
This paper considers a configuration problem for a manufacturer’s supply network in the presence of volume discounts. An integrated mixed-integer nonlinear programming (MINLP) model is developed to simultaneously determine the selection of suppliers and production levels under an uncertain demand environment. The suppliers provide discounts in terms of the total value of purchased items instead of the quantity of items. The objective of the model is to maximize the manufacturer’s expected profit, subject to both manufacturer and supplier capacities. An external function is developed to deal with integral parts of the model and is integrated with the general algebraic modeling system (GAMS) and its solvers to solve the complex problem. Two numerical examples are used to illustrate the effectiveness of the proposed model and solution approach. Management insights from the sensitivity analysis and comparisons of volume discount are also discussed.